2000
DOI: 10.1161/01.cir.101.13.1559
|View full text |Cite
|
Sign up to set email alerts
|

Results of Maze Surgery for Lone Paroxysmal Atrial Fibrillation

Abstract: This pilot study demonstrates the effectiveness and safety of maze III surgery for lone PAF. In patients without sick-sinus syndrome, this intervention offers a sensible alternative to His bundle ablation and lifelong pacemaker dependency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 30 publications
0
39
0
3
Order By: Relevance
“…In fact, even if the mortality-and-stroke-rate benefit of maze over non-maze has not yet been proved, 25,26 it is reasonable to assume that the restoration of sinus rhythm improves the quality of life and perhaps survival prospects. 15,27 In our judgment, such a gain could be related to the progressive improvement of heart-chamber size and contractile performance. Indeed, our subgroup of 84 mitral patients showed a significant midterm persistence of left atrial area and of indexed LV end-diastolic volume improvement, an entity superior to that previously reported even in cases of optimal mitral valve repair.…”
Section: Lvef 12 Months After Maze (%)mentioning
confidence: 82%
“…In fact, even if the mortality-and-stroke-rate benefit of maze over non-maze has not yet been proved, 25,26 it is reasonable to assume that the restoration of sinus rhythm improves the quality of life and perhaps survival prospects. 15,27 In our judgment, such a gain could be related to the progressive improvement of heart-chamber size and contractile performance. Indeed, our subgroup of 84 mitral patients showed a significant midterm persistence of left atrial area and of indexed LV end-diastolic volume improvement, an entity superior to that previously reported even in cases of optimal mitral valve repair.…”
Section: Lvef 12 Months After Maze (%)mentioning
confidence: 82%
“…According to the literature, the sinus rhythm in patients with paroxysmal AF can be observed after ablation in more than 90-95% of cases during out-patient clinical examinations 17 . Sinus rhythm is usually restored in 60-80% of patients with originally permanent AF [18][19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative arrhythmias may include transient and self-limited or sustained atrial fibrillation [1][2][3][4][5][6][7][8][9][10][11][12] or regular tachycardias related to macroreentry or focal mechanisms. [13][14][15] Other than typical atrial flutter, the most commonly reported reentrant tachycardia after surgery for atrial fibrillation involves the coronary sinus musculature to support reentry around the mitral valve annulus.…”
mentioning
confidence: 99%